Costurando narrativas pelos fios da coordenação pedagógica em contexto curricular da educação infantil - AGUIAR, Maria José de Melo e Alvim (2021)
The weaving of this research takes place in the sewing of a study on the pedagogical coordinator, understood as the subject of narratives, which cross his self-formative path when developing activities in the scope of Early Childhood Education, and the curriculum, as a cultural artifact that takes place in the inter-social and pedagogical relations. The interest in research echoes the need to communicate experiences in the formative dynamics of the coordinator's activities and knowledge, as a professional who needs to be known in the course of his formative life and culminates in the defining question of the research: “how the pedagogical coordinator can develop his activities in front of to the curriculum of Early Childhood Education enhanced by its autobiographical writing?”. The main objective is to get to know the pedagogical coordinator in his activities along with the curriculum through the autobiographical narrative with a view to the construction of an educational product. And, it unfolds in the specific objectives that aim: to investigate the history of pedagogical coordination in the midst of its pedagogical activities before the curriculum of Early Childhood Education; identify the interrelation of the autobiographical perspective as a self-formative strategy with the pedagogical coordinator; to build a Narrative Notebook in collaboration with a pedagogical coordinator to contribute to its self-formative path. This research with a qualitative approach establishes a methodology under the bibliographic and documentary bias through the literature review anchored in studies by Giroux (1986), Cunha (1997), Kramer and Souza (2003), Libâneo (2004), Horta (2007), Gomes (2009), Placco and Souza (2012), Placco and Almeida (2012), Goodson (2018) and the most current documents of Early Childhood Education (DCNEI; BNCCEI), and the research by Benjamin (1987), Larrosa (2002), Josso (2007), Jovchelovitch and Bauer (2010), Sousa and Cabral (2015) and Souza and Meireles (2017), lead it to the autobiographical approach, having autobiographical letters to collect information about the pedagogical coordinator who assumes himself as the research subject, using ICT tools (email and whatsapp), to the detriment of the Covid-19 pandemic. After collecting and systematizing the data, a descriptive and interpretive analysis was carried out, respecting representations and apprehensions placed by the writings of the self, coming to compose the construction of the educational product, which brings within the scope of its structure the compilation of suggestions to the process. of selftraining, mediated in the coordinator's continuing education through autobiographical letters, as material for the continuation of future research in the narrative / autobiographical perspective.